Vakuumsko indukcijsko taljenje - Zupanič, Franc (Vakuumist, 2007)
Vacuum induction melting (VIM) is used for melting of metallic materials by using electrical induction under vacuum conditions. The process is appropriate for almost all metallic materials and is preferentially used for primary melting of alloys that contain very reactive elements (superalloys, titanium alloys, tool and magnetic steels). It assures high yield of reactive alloying elements and reproducible attainment of required chemical composition. VIM is also inevitable for production of demanding high-performance alloys that must contain very small amounts of gases, harmful trace elements and non-metallic inclusions. Despite numerous advantages of VIM the quality of castings is often insufficient for highly demanding applications, therefore castings must be remelted (e. g. by vacuum arc remelting and electron beam melting) and exposed to forming operations.
Keywords: taljenje; vakuumsko taljenje; zlitine